2019
DOI: 10.1007/s11440-019-00808-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling coupled erosion and filtration of fine particles in granular media

Abstract: One of the major causes of instability in geotechnical structures such as dikes or earth dams is the phenomenon of suffusion including detachment, transport and filtration of fine particles by water flow. Current methods fail to capture all these aspects. This paper suggests a new modeling approach under the framework of the porous continuous medium theory. The detachment and transport of the fine particles are described by a mass exchange model between the solid and the fluid phases. The filtration is incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(22 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Additionally, numerical simulations [e.g. 16,17] and micro-scale images [e.g. 18,19] were also used to study the internal instability.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, numerical simulations [e.g. 16,17] and micro-scale images [e.g. 18,19] were also used to study the internal instability.…”
Section: Introductionmentioning
confidence: 99%
“…A finite difference code was developed to investigate the validity of the proposed model . The comparison between experimental results and simulations demonstrated that, with an appropriate erosion law and well‐calibrated model parameters, the numerical model was able to reproduce with success the initiation and development of internal erosion.…”
Section: Coupled Hydromechanical Modelmentioning
confidence: 99%
“…For examples, Üzüm et al (2009) synthesized and characterized Kaolin-supported nZVI (K-nZVI) [33], while Zhang et al (2010) demonstrated the removal of Pb(II) from water using K-nZVI [34], However, the effect of kaolin particle size on the pollutant removal performance has not been well studied in the literature. The present authors believe that as the particle size of kaolin decreases, the specific surface area, the number of pores, and the pore volume will increase [35,36]. The resulting increase in adsorption capacity will allow more nZVI to be loaded on the surface of kaolin, which should improve the removal efficiency for Pb(II) in water.…”
Section: Introductionmentioning
confidence: 76%